Liquidity crises and the international financial architecture - Ilan Goldfajn; Rodrigo O. Valdes (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1999)
The paper analyzes the effect of different proposals for the new international financial architecture in an open economy liquidity crises model. It shows that an international lender of last resort that provides a complete financial rescue leads, in the short run, to a lower probability of a BoP crises and financial runs. However, the perverse incentives of a complete bailout lead to an increasing probability offinancial runs in the long run. A partial financial package may not reduce the probability of financial runs and twin crises. Private sector participation rules can increase the probability of finan- cial runs and twin crises if a large proportion of foreign investors expect to withdraw their investment without loss.
Keywords: F32; F33; 330